Investigating the effects of novel hay presentation for bighorn sheep (Ovis canadensis) in managed care - Randall, Sydney, author; Willis, Jennie, advisor; Matlock, Sarah, committee member (Colorado State University. Libraries, 2025)
For many ungulate species including horses (Rochais et al., 2018), cattle (Redbo & Nordblad, 1997), and giraffe (Koene, 1999), the benefits of feeding enrichment in replicating natural foraging behavior have been demonstrated. Ruminant species such as cattle (Van Os et al., 2018) have also been shown to demonstrate contrafreeloading when feeding enrichment is presented. Contrafreeloading behavior as well as novelty may impact the amount of interactions with feeding enrichment. The effects of feeding enrichment for Ovis canadensis in managed care have not been studied. In this study, Ovis canadensis housed at the Colorado Parks and Wildlife Foothills Wildlife Research Facility were presented with hay bags in addition to ad libitum hay and their behavior was recorded using scan sampling. This data was used to address three questions: do bighorn sheep spend more time engaged in feeding behavior when hay bags are present, do they spend more time foraging ad libitum or from a hay bag, and do they interact more with the hay bag when it is new to the environment? Results suggest that bighorn sheep do spend more total time engaged in feeding behavior when a hay bag is present in addition to ad libitum forage and they interact more often with a novel hay bag. For one pen studied, results suggest the bighorn sheep housed there prefer the hay bag to ad libitum hay.
Keywords: hay bag enrichment; novel enrichment